Comparison of fixation systems for anterior cruciate ligament rupture reconstruction at Hospital Nacional de Policia - Martínez Villanueva, Jimmy Vladimir (2017)
Introduction: The anterior cruciate ligament rupture is common and produces great knee instability; reconstruction is the ideal treatment. Objective: To determine the functional evolution of patients undergoing anterior cruciate ligament reconstruction with external anchoring and internal expansion systems. Design: Analytical, observational, longitudinal and ambispective study. Location: Orthopedics and Traumatology Department, Hospital Nacional de Policía “Luis Nicasio Saenz”, Lima, Peru. Participants: All patients who met the inclusion and exclusion criteria from January to December 2014. Interventions: Data collection was based on medical history, physical examination and application of the Lysholm and Tegner Knee Scoring Scales at baseline and after 6 and 12 months follow-up. Results were analyzed with descriptive and inferential statistics with the Shapiro-Wilk and Mann-Whitney U tests for nonparametric variables. Results: 46 patients were included, 38 men and 8 women; the mean age was 31.7 years; 13 patients received an internal expansion system and 33, an external anchoring systems were placed. There were no medical complications. Lysholm Knee Scoring Scale showed an increase from 65.2 points (poor) on average in the preoperative assessment to 88.0 points (good) 12 months later; Tegner Activity Scale showed 7 points in 42 patients and 8 points in 4 patients (middle physical activity level). There was no significant difference on functional recovery between the two systems. Conclusions: Both internal expansion and external anchoring fixation systems had good results by improving the knee function from poor to good after surgery.